Representation of Complex Characters and Children's Agency in the Short Story "Journey of the Moon" through Maria Nikolajeva's Perspective - Zahro, Fatimatuz; Indriyani, Jiphie Gilia (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
Children's literature is frequently confined to static character stereotypes and didactic optimism. This study aims to analyze the depiction of the complex character of Rembulan in the short story Perjalanan Rembulan through the application of Maria Nikolajeva’s children's literature theory. Employing a qualitative descriptive method with in-depth textual analysis, the research explores how the narrative constructs aesthetic engagement through the portrayal of intelligence, patience, and perseverance. The findings reveal that Rembulan is not a static figure but rather a multidimensional subject who undergoes significant character transformation as her chronic illness progresses. Through Nikolajeva’s perspective, it is discovered that Rembulan’s patience functions as both a psychological survival strategy and an emotional "mask" to satisfy social expectations. The narrative climax, depicting the character's surrender at the terminal stage, demonstrates narrative courage in rejecting conventional happy endings while evoking profound narrative empathy in readers. The study concludes that character complexity in children's literature serves as an effective medium for fostering empathy and an understanding of harsh life realities for the younger generation.